2021
DOI: 10.1111/acem.14245
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict which COVID‐19 patients will need transfer to intensive care within 24 hours of floor admission?

Abstract: Background: Patients with COVID-19 can present to the emergency department (ED) at any point during the spectrum of illness, making it difficult to predict what level of care the patient will ultimately require. Admission to a ward bed, which is subsequently upgraded within hours to an intensive care unit (ICU) bed, represents an inability to appropriately predict the patient's course of illness. Predicting which patients will require ICU care within 24 hours would allow admissions to be managed more appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The median (quartiles) of the CT score at ICU admission in the oxygen therapy group was 10 [ [7] , [8] , [9] , [10] , [11] , [12] ], which was significantly lower than that [18 [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]] in the MV group ( P < 0.0001). A significant negative correlation ( r = −0.6) was detected between SpO 2 on room air and the CT score ( P < 0.0001).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The median (quartiles) of the CT score at ICU admission in the oxygen therapy group was 10 [ [7] , [8] , [9] , [10] , [11] , [12] ], which was significantly lower than that [18 [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]] in the MV group ( P < 0.0001). A significant negative correlation ( r = −0.6) was detected between SpO 2 on room air and the CT score ( P < 0.0001).…”
Section: Resultsmentioning
confidence: 93%
“…In the present study, we evaluated SpO 2 on the room air rather than on oxygen because the determination of FiO 2 remains inaccurate and influenced by minute ventilation, air leak, and breathing pattern in patients receiving oxygen through a facemask. Few studies had evaluated the validity of baseline SpO 2 as an important risk factor in COVID-10; however, most of these studies used SpO 2 as a component of multivariate prediction models [ [14] , [15] , [16] ] and did not use the need to ventilatory support as the primary outcome. Pre-hospital lowest SpO 2 had been evaluated for triaging of patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Specific severity rules have also been developed for ED populations, including the Quick COVID‐19 Severity Index and PRIEST score. 10 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…A living systematic review has identified more than 100 prognostic models, 19 including the 4C mortality score and the QCOVID living risk prediction algorithm 17,18 . Specific severity rules have also been developed for ED populations, including the Quick COVID‐19 Severity Index and PRIEST score 10,22,23 …”
Section: Discussionmentioning
confidence: 99%
“…We were very interested to read the study by Wang et al 1 on predicting which ED patients with COVID‐19 will require escalation to intensive care unit within 24 hours of admission. They identified risk factors and developed triage models for the ED physician based on presenting history, signs, and symptoms.…”
mentioning
confidence: 99%